SESQUITERPENE LACTONES FROM PLANTS OF THE ASTERACEAE FAMILY AS THE POTENTIAL SOURCE OF ANTI-TUMOUR AGENTS - Klochkov, S.; Bachurin, S.; Bulychev, Y.; AfanaÂ´seva, S. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
The plants of the Asteraceae family are actively applied in national medicines for the treatment of a wide spectrum of diseases, including oncological ones. In this work chemical compositions of Inula britannica, caspica, hirta, and helenium have been studied. The high quantity of sesquiterpene lactones amounting up to 3-6 % of dry plant biomaterials was shown. In addition to the essential chemical diversity, this fact gives a real base for large scale isolations of various scaffolds followed by their chemical modification [1]. More then 150 novel modified sesquiterpene lactones, including water-soluble forms and containing different pharmacophoric fragments, were synthesized. Synthesized derivatives were tested as potential cytotoxic agents against a standard panel of human tumour cell lines using the MTT assay. Compounds with a high level of non-specific cytotoxic activity may be found very frequently within all lactones, natural and modified ones. More potent was SLD-41730 with cytotoxicity towards leukemia cell lines - GI50 values were 10-7 – 10-8 M. Probable mechanism of sesquiterpene lactones action is the apoptosis induction through the inhibition of the key enzyme farnesyltransferase. Natural and modified lactones were tested using the original spectrofluorometric method, the evaluation of the farnesyltransferase activity. Inhibition activity of hit-compounds was comparable to the level of known inhibitors: IC50 range was about 0,3-5 mM. High levels and frequency of cytotoxic activity of sesquiterpene lactones demonstrated the outlook of further modification of these scaffolds and hit within the hit-to-lead program and on their screening based on further mechanisms. References: 1. Klochkov et al., Chemistry of Natural Compounds, Vol. 42, No. 4, 2006, p.400